GAMIFIED EDUCATIONAL APPS AND READING COMPREHENSION IN HOME-SCHOOLED CHILDREN: AN EXPLORATORY MIXED-METHODS CASE STUDY - Budianto Hamuddin; Aprilia Yunda Supasa; Meutya Rizki Ramadhani (University of Kuningan, 2026)
Many children now encounter stories on digital screens rather than on printed pages, yet limited empirical evidence exists regarding how gamified reading applications support comprehension in home schooling environments. Addressing this gap, this small scale mixed methods case study examined a four weeks intervention involving selected gamified reading applications used by two home schooled children aged ten and eleven. A standardized reading comprehension test was administered before and after the intervention to provide descriptive indicators of change in overall comprehension and three subskills, namely vocabulary, literal comprehension, and inferential comprehension, while semi structured interviews with the children and their parents were thematically analysed to explore learning experiences, engagement patterns, and contextual factors shaping app use. In this exploratory study with two participants, overall comprehension scores increased from a mean of 57.5 before the intervention to 74.0 afterwards. Vocabulary scores rose from 53.5 to 74.0, literal comprehension from 60.0 to 78.0, and inferential comprehension from 50.0 to 66.0, indicating observable descriptive gains across the three components of reading comprehension during the intervention period. Qualitative findings suggested increased motivation and sustained engagement with reading tasks, while parents emphasized that active guidance was often required to redirect attention from game rewards toward text meaning and deeper comprehension processes. Taken together, the findings provide preliminary and context specific insights from a rarely documented home schooling setting. Rather than offering generalizable conclusions, this study presents exploratory evidence that gamified reading applications may support certain aspects of reading development when their use is regular, text focused, and accompanied by parental scaffolding, while also generating hypotheses and nuanced considerations for parents, educators, and educational technology designers interested in integrating gamified tools into home based literacy practices.